2008
DOI: 10.1007/s10592-008-9524-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lespedeza germplasm genetic diversity and its phylogenetic relationship with the genus Kummerowia

Abstract: The genetic diversity of the genus Lespedeza is not well known and the phylogenetic relationship of Lespedeza with the genus Kummerowia is unclear. We report the first study in which polymorphic expressed sequence tag-simple sequence repeat (EST-SSR) markers derived from Medicago, cowpea and soybean were used to assess the genetic diversity of the USDA Lespedeza germplasm collection and clarify its phylogenetic relationship with the genus Kummerowia. Phylogenetic analysis partitioned 44 Lespedeza accessions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…and D. microphyllum (Thunb.) DC., were additionally included as outgroups following Nemoto et al (1995) and Wang et al (2009). Desmodium was resolved as sister to the clade containing Campylotropis, Kummerowia, and Lespedeza (Doyle et al, 2000;Ohashi, 2005;Stefanovic et al, 2009).…”
Section: Taxon Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…and D. microphyllum (Thunb.) DC., were additionally included as outgroups following Nemoto et al (1995) and Wang et al (2009). Desmodium was resolved as sister to the clade containing Campylotropis, Kummerowia, and Lespedeza (Doyle et al, 2000;Ohashi, 2005;Stefanovic et al, 2009).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Phylogenetic analysis based on EST-SSR markers reveals Kummerowia to be non-monophyletic. Two accessions of the genus sampled are embedded within a paraphyletic Lespedeza (Wang et al, 2009). Recent phylogenetic analyses based on DNA sequences of chloroplast and nuclear genes of 7-36 accessions of Lespedeza separates Campylotropis from Kummerowia and Lespedeza, while the latter two genera remain unresolved (Stefanovic et al, 2009;Nemoto et al, 2010;Han et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Using EST-SSR markers derived from Medicago, cowpea and soybean, the genetic diversity of the USDA Lespedeza germplasm collection was assessed and its phylogenetic relationship with the genus Kummerowia was clarified (Wang et al, 2009b), despite the fact that phylogenetic analysis with morphological reexamination provides a more complete approach to classify accessions in plant germplasm collection and conservation. Orsini et al (2004) Rout et al (2008) assessed the phylogenetic relationships of Indian goats using 17 microsatellite markers.…”
Section: Population and Phylogenetic Relationshipsmentioning
confidence: 99%
“…Lespedeza was not monophyletic using ITS sequence variation of 10 species of Lespedeza from China. Wang et al (2009 ) found that Kummerowia is embedded within Lespedeza using expressed sequence tag-simple sequence repeat (EST-SSR) markers. Most recently, Nemato et al (2010 ) and Han et al (2010 ) inferred that subgen.…”
mentioning
confidence: 99%